Comparative analysis of sexual harassment between male and female nurses: A cross‐sectional study in Greece. (29th July 2021) - Papantoniou, Panagiotis
Abstract: Aims: The aims of this work are to compare the frequency of sexual harassment among male and female nurses in Greece and capture the reasons for not reporting sexual harassment. Background: The #MeToo and #TimesUp movements have emphasized the ubiquity of sexual harassment in health care. Yet, limited studies have explored sexual harassment among male and female nurses and the reasons for not reporting it. Methods: An online cross‐sectional survey was conducted using the Sexual Experiences Questionnaire (SEQ) to collect data from 1.264 female nurses and 507 male nurses. Results: Sixty‐seven per cent of female nurses have experienced sexual harassment at least once in their working lives, whereas male nurses' exact figure was 41%. The most common type of sexual harassment for both groups was gender harassment, followed by unwanted sexual attention and sexual coercion. Female nurses experienced more severe adverse consequences, whereas male nurses experienced moderate negative consequences. Conclusions: Policymakers and hospital managers should create mechanisms to allow victims to report their experiences and establish an independent committee to assess victims' complaints. Implications for nursing management: Managers are called to change how hospitals deal with sexual harassment cases, modernize their management style, and support sexual harassment victims to break their silence without fear of negative consequences.